ENGLISH READING MATERIALS DEVELOPMENT FOR STUDENTS OF SMAN 1 KABANJAHE - Benny - Ichsanda; Anni Holila Pulungan (Universitas Negeri Medan, 2014)
Abstract Karo Regency is a potential tourism region to visit. It has so many natural beauty and also cultural uniqueness. Therefore, the government should prepare the potential human resources (SDM) to face this potency. One important thing government should prepare is the English materials students learn, in order the students can understand it well, so they can apply it in their daily life in facing the foreign tourists come. However, the materials they use are not appropriate to their needs. Therefore, it is needed to develop the English reading materials for students. Research and Developmental (R & D) is the suitable way to develop the materials. Based on the evaluation, the materials teachers use in educating the students are not appropriate to the students needs. It can be seen from the questionnaires distributed to the students that they need authentic materials. Also from interviewing the teachers and practitioners, it can be seen that students need the materials which are related to their region and daily life. The report text and narrative text materials such as “Persimmon” and “Pawang Ternalem” are the example of appropriate materials to the students because it is representative to their daily life. Based on the results of the study, conclusion and suggestions are directed to the teachers who are teaching in SMAN 1 especially and in Karo regency generally to create the materials based on region culture and potency which will be taught to the students in order the students can understand it well and can apply it in their daily life in facing the tourists come to their region. Keywords: Development, Reading, Materials